1977
DOI: 10.1017/s0033291700029408
|View full text |Cite
|
Sign up to set email alerts
|

Neurotic illness in the families of children with asthma and wheezy bronchitis: a general practice population study

Abstract: synopsisIn a controlled population study 111 families of children with asthma and wheezy bronchitis were screened. The mothers of asthmatics suffered more depressive illness than controls. This correlates with the severity of the child's asthma. There was no difference in immunological status between depressive and non-depressive mothers of asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
0
10
1
Order By: Relevance
“…These data may be useful for understanding the nature of the association between childhood asthma and maternal depression. Additionally, the diagnosis and severity classification of asthma was made by a specialist, but not based solely on the parent's report of symptoms as in previous studies (2,5,6). Accurate diagnosis of asthma in this study may increase the validity of its conclusions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These data may be useful for understanding the nature of the association between childhood asthma and maternal depression. Additionally, the diagnosis and severity classification of asthma was made by a specialist, but not based solely on the parent's report of symptoms as in previous studies (2,5,6). Accurate diagnosis of asthma in this study may increase the validity of its conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…The sample size was determined on the assumption that prevalence of depression was 35% among mothers of children with asthma and 12% among mothers of children without asthma (5,6,8). We recruited 2 non-exposed participants for each exposed participant, and our sample size calculation (power = 95%, alpha level = 0.05) determined that we would need to include at least 70 mothers of children with asthma and 140 mothers of children without asthma.…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The initial evidence for this link came from mothers whose children had asthma but did not have MDD [26,27]. In some studies, rates of depression in family members were related to the severity of the child's asthma symptoms, raising the possibility that these were related to the stress of having an ill child [28,29].…”
Section: Relationships Between Asthma and Psychiatric Illnessmentioning
confidence: 99%
“…15 Studies have also indicated that in caregivers, especially mothers, life stressors and depression are associated with worse pediatric asthma symptom severity and overall morbidity. 15,16 Further, Weil et al found that children of caregivers with mental health problems were almost twice as likely to require hospitalization for their asthma. 13 Depression also can impact one’s ability to comprehend information and communicate effectively.…”
Section: Introductionmentioning
confidence: 99%